Financial Transaction Tax and Economic Crisis: is it Time for a Tax on International Transactions? - Adamy, Pedro (Revista de Direito Tributário Internacional Atual, 2019)
This paper aims at the legal problems that arise concerning the introduction of a financial transaction tax. The article analyzes the impact, characteristics and challenges of a tax on international financial transactions and its relationship to economic crises.